Use of plastic geocellular modules as a replacement gravel layer for natural turf rootzones. Issue 1 (15th January 2022) - Young, Thomas; Mann, Ruth; Spring, Christian
Abstract: A trial was conducted to assess the suitability of a novel plastic geocellular drainage layer (Permavoid) as a replacement for a conventional gravel layer in a high‐quality sports pitch. The trial was conducted during the 2014–2015 and 2015–2016 United Kingdom football (soccer) seasons. Perennial ryegrass ( Lolium perenne L.) was grown under five different rootzone depth treatments (50, 100, 200, and 300 mm over Permavoid and 300 mm over gravel as a control representing current practices). These were repeated for two contrasting rootzone types. The trial area was subjected to artificial football‐style wear throughout each playing season, with irrigation and nutritional inputs as would be normal for a high‐quality football pitch. Infiltration rates, rootzone moisture content, turf cover and tractional strength for the 200‐ to 300‐mm rootzone over Permavoid and 300 mm over gravel were the same throughout the trial. The replacement of the gravel drainage layer with Permavoid had no negative effect on the rootzone's hydraulic characteristics or turfgrass growth over the 2‐yr study period. In addition, it may be possible to use shallower rootzone depths in some circumstances, reducing the volume of material needed for construction. Shallower rootzones (50–100 mm) experienced greater fluctuations in rootzone moisture content, which was likely to be directly related to rootzone depth. Rootzone type had a minor effect, with finer rootzones holding onto more moisture and allowing slightly stronger turf. Therefore, when managing shallower and/or coarser rootzones, maintenance programs need to reflect the moisture and nutrient retention characteristics of these growing media. Core Ideas: A conventional sports pitch gravel layer can be replaced with geocellular modules. The drainage performance of rootzones above geocellular modules was not compromised. All profiles tested showed acceptable turfgrass growth and performance. The rootzone depth of a sports pitch can be reduced to minimize material use. Geocellular systems give drainage layers additional stormwater storage functionality.